What Is Bioethics Worth? - Solomon, Mildred Z. (The Hastings Center report, 2016)
What is bioethics to do when it strives to assess the quality of its research and scholarship and when it needs to justify its work to prospective funders, especially a funder like the National Institutes of Health that privileges empirical discovery? In “A Conceptual Model for the Translation of Bioethics Research and Scholarship,” Debra Mathews and colleagues take an important first step at advancing an answer. The authors describe what they call a translational process, whereby bioethics “outputs” are translated into changes of three types: in thinking, practice, and policy. It goes nearly without saying that bioethics research and scholarship must be held accountable for changes in thinking. What raison d'etre do we have if not to deepen thinking, question assumptions, and encourage ourselves and others to examine hard issues from novel approaches? Assuredly it is hard to assess quality, and even harder to assess specific changes in thinking for which high-quality scholarship may be responsible, but it is a necessary goal and one for which we should strive without reservation. Bioethics should also affect policy and practice. We should document how it does and the extent to which it does as often and as prominently as possible. However, let us be wary of pinning too much on practice and policy changes as the primary way of establishing bioethics’ worth.